Critical thinking and reflective practice in the science education practicum in Kuwait - AL-HASHIM, A. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThis is a speculative paper linking critical thinking to reflective practice in science education teaching practicum for the prospective teachers of science in Kuwait. The writer has identified that student teachers lack in a critical thinking approach to teaching sciences, promoting science literacy, and critically linking science to society and technology, definition of critical thinking has  been interpreted in a context of reflective practice, with a redefinition of the factors contributing to unexamined, uncritically absorbed assumptions about teaching and learning. The paper has also shed light on how critical thinking can be evaluated in the teaching practice component.RESUMENEste es un documento especulativo que vincula el pensamiento crítico con la práctica reflexiva en la práctica de la enseñanza de la educación científica para los futuros profesores de ciencias en Kuwait. El escritor ha identificado que los estudiantes docentes carecen de un enfoque de pensamiento crítico para enseñar ciencias, promover la alfabetización científica y vincular críticamente la ciencia con la sociedad y la tecnología. La definición del pensamiento crítico se ha interpretado en un contexto de práctica reflexiva, con una redefinición de los factores, contribuyendo a suposiciones no examinadas, absorbidas sin crítica sobre la enseñanza y el aprendizaje. El documento también ha arrojado luz sobre cómo se puede evaluar el pensamiento crítico en el componente de práctica docente.